Freedom national : the destruction of slavery in the United States, 1861-1865 - Oakes, James, 1953- (W.W. Norton & Company, Inc., 2013)
"Traces the history of emancipation and its impact on the Civil War, discussing how Lincoln and the Republicans fought primarily for freeing slaves throughout the war, not just as a secondary objective in an effort to restore the country."
Keywords: Spojené státy americké. -- Prezident (1861-1865 : Lincoln); monografie; monographs; 1861-1865; 1861-1870; otroctví -- Spojené státy americké; dějiny otroctví -- Spojené státy americké; zrušení otroctví -- Spojené státy americké -- 1861-1870; americká občanská válka (1861-1865); slavery -- United States; history of slavery -- United States; abolition of slavery -- United States -- 1861-1870; American civil war (1861-1865); Spojené státy americké -- dějiny -- 1861-1870; United States -- history -- 1861-1870